A Child Is a Child - Weninger, Brigitte (New York Penguin Young Readers Group, 2004)
When Daddy and Mama Frog disappear, two little frog children are left all alone. The other animals would like to help, but no one knows how. When Mama Mouse shows up and agrees to take the little frogs in, she simply says, "A child is a child, and all children need a place to live and play, good food and someone who loves them."
K - 2
Keywords: Frogs - Fiction; Mice - Fiction